Persulfate initiated ultra-low cross-linked poly(N-isopropylacrylamide) microgels possess an unusual inverted cross-linking structure. Issue 17 (1st April 2016) - Virtanen, O. L. J.; Mourran, A.; Pinard, P. T.; Richtering, W.
Abstract : Ultra-low cross-linked poly( N -isopropylacrylamide) microgel particles are hollow in contrast to the fuzzy sphere structures usually associated with microgels. Abstract : Cross-linking density and distribution are decisive for the mechanical and other properties of stimuli-sensitive poly( N -isopropylacrylamide) microgels. Here we investigate the structure of ultra-low cross-linked microgels by static light scattering and scanning force microscopy, and show that they have an inverted cross-linking structure with respect to conventional microgels, contrary to what has been assumed previously. The conventional microgels have the largest polymer volume fraction in the core from where the particle density decays radially outwards, whereas ultra-low cross-linked particles have the highest polymer volume fraction close to the surface. On a solid substrate these particles form buckled shapes at high surface coverage, as shown by scanning force micrographs. The special structure of ultra-low cross-linked microgels is attributed to cross-linking of the particle surface, which is exposed to hydrogen abstraction by radicals generated from persulfate initiators during and after polymerization. The particle core, which is less accessible to the diffusion of radicals, has consequently a lower polymer volume fraction in the swollen state. By systematic variation of the cross-linker concentration it is shown that the cross-linking contribution from peroxide under typical synthesis conditions is weaker than that from the use of 1 mol% N, N ′-methylenebisacrylamide. Soft deformable hydrogel particles are of interest because they emulate biological tissues, and understanding the underlying synthesis principle enables tailoring the microgel structure for biomimetic applications. Deformability of microgels is usually controlled by the amount of added cross-linker; here we however highlight an alternative approach through structural softness.